Dining room and banquet management - Strianese, Anthony J.; Strianese, Pamela P. (Australia : Thomson Delmar Learning, 2003)
"This best-selling restaurant management text is designed to prepare you for managing dining rooms and banquets in restaurants, hotels, and resorts. The first section emphasizes the history, importance, and proper guidelines of service along with the appearance and sanitation of the restaurant and its staff. The second section is designed to demonstrate proper methods of managing service in an a la carte restaurant. The final section includes how to effectively manage banquets. This book is a combination of established research, personal observations and interviews with successful individuals who excel in providing excellent service in dining room and banquet management." "Key features: a "hands-on" text that offers step-by-step instruction; effective service techniques for both a la carte and banquets; helpful hints, suggestions, and tips are offered throughout; and all-new and integrated material on sanitation."
Foreword -- Preface -- Acknowledgments -- Part 1. The Food Service Industry -- Chapter 1. The Importance of Service -- Chapter 2. The Importance of Sanitation and Appearance -- Chapter 3. Styles of Service and Place Settings -- Chapter 4. Proper Guidelines for Service -- Chapter 5. The Styles of Service -- Part 2. Dining Room Management -- Chapter 6. Training the Service Staff to Serve the Meal -- Chapter 7. Organizing the Dining Room to Accept Guests -- Chapter 8. Planning Reservations and Blocking Tables -- Chapter 9. Managing the Dining Experience -- Part 3. Banquet Management -- Chapter 10. The Banquet Business and the Banquet Manager -- Chapter 11. How to Book Functions -- Chapter 12. The Banquet Function Sheet -- Chapter 13. Managing the Function --
Includes index.
Keywords: FOOD SERVICE MANAGEMENT